2007
DOI: 10.1007/s10750-006-0398-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in fish community structure of a marine embayment in Zanzibar, Tanzania

Abstract: Spatial and temporal variation in the fish community structure were studied in a tropical non-estuarine embayment in Chwaka Bay, Zanzibar (Tanzania). Fish samples were collected bi-monthly (at each spring low tide) for 1 year (November 2001-October 2002) from a range of bay habitats ranging from mangroves deep inside the bay to seagrass beds close to the mouth of the bay. Additionally, environmental variables were examined to determine their relationship with the fish community structure. Being a non-estuarine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 43 publications
5
27
0
2
Order By: Relevance
“…(a few here), emperors (a dominant), and monos (another dominant. Fish density and biomass decreased from January to February (Lugendo et al 2007), similar to our observations. Species richness increased slightly from Wetlands Ecol Manage (2009) 17:345-354 351 January to February and then decreased during the rainy season; this was attributed to altered salinity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(a few here), emperors (a dominant), and monos (another dominant. Fish density and biomass decreased from January to February (Lugendo et al 2007), similar to our observations. Species richness increased slightly from Wetlands Ecol Manage (2009) 17:345-354 351 January to February and then decreased during the rainy season; this was attributed to altered salinity.…”
Section: Discussionsupporting
confidence: 91%
“…In Zanzibar, barracuda (Sphyraena barracuda) (Walbaum) recruits decreased from January to February, while the pickhandle barracuda, S. jello, increased in the present study. Lugendo et al (2007) noted an increase in small monos and a decrease in larger individuals from January to February, which was observed here. Four of the seven species they studied had recruits in the mangroves in January and February, which corresponds to this study in which monos, surgeons, butterflyfish and emperor recruits appeared in late January.…”
Section: Discussionsupporting
confidence: 87%
“…The height and biomass of pneumatophores as well as canopy shade (presented as relative light intensity both inside and outside the vegetated area) were important factors influencing species richness, density, and biomass in our study, suggesting that pneumatophores and trees might provide refuge for fish to escape predation (Laegdsgaard and Johnson 2001). Besides, studies have shown relationships between fish assemblages and water salinity (Barletta et al 2005, Lugendo et al 2007), water temperature (F elix et al 2017), access to creeks (Meynecke et al 2008, Krumme et al 2014, and habitat heterogeneity (F elix et al 2017), etc. At the Avicennia site, structure of pneumatophores had impacts on all measured fish variables, with pneumatophore height showing positive effect but pneumatophore biomass showing negative effect.…”
Section: Structural Complexity Of Mangroves and The Spatial Patterns mentioning
confidence: 56%
“…All replicates of the study were performed during the wet season; fish abundance in inshore habitats usually peaks on a seasonal basis (Stoner 1986;Barietta et al 2003;Lugendo et al 2007). …”
Section: Site Descriptionmentioning
confidence: 99%